The Effect of Baby Massage on Decline Bilirubin Levels in Icteric Babies - Fatwa, Dyah Mayasari; Lelasari; Fatin, Cheryl Sylfia; Hasanah, Nidaul; Khoerunnisa, Lela Fauziah (Postgraduate, University of Mataram, 2024)
Indirect hyperbilirubinemia is one of the conditions that most affects the health of newborns throughout the world, occurring in 60% of term newborns and 80% of premature newborns. Baby massage has emerged as an effective method in treating jaundice babies. This study aims to determine the effect of baby massage on reducing bilirubin in icteric babies. The method used was pre-test and post-test with a control group (quasi-experiment with control). The study population consisted of 120 icteric babies treated in hospitals in the Banten and West Java regions in June 2024, with a sample of 92 babies selected using purposive sampling. The results showed that in the intervention group, the average baby bilirubin level before massage was 16.4 mg/dL and after massage it was 11.9 mg/dL. In the control group, the average bilirubin level before massage was 17.7 mg/dL and after massage it was 10.6 mg/dL. There was a significant difference in the reduction of bilirubin levels in icteric babies who were given and not given breast milk in the intervention group (p-Value=0.008 and p-Value=0.000). The conclusion of this study is that baby massage has a significant effect on reducing bilirubin levels in icteric babies, both in the intervention and control groups (p-Value=0.000). Therefore, infant massage is recommended as part of the care of babies with neonatal hyperbilirubinemia, but it must still be done with caution.